2016
DOI: 10.1177/1753193416677712
|View full text |Cite
|
Sign up to set email alerts
|

Recovery, responsiveness and interpretability of patient-reported outcome measures after surgery for Dupuytren’s disease

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…MCID refers to the smallest change in status that patients consider important. Estimated MCID values for the URAM scale in the literature are 2.9 points for patients treated with NA (Beaudreuil et al 2011) and 10.5 points for those treated with open surgery (FSC or dermofasciectomy) (Rodrigues et al 2017). The results of our meta-regression analysis are consistent with these results, as we detected an improvement of 1.67 points in the URAM scale for each change in Tubiana stage (improvement of approximately 45º).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…MCID refers to the smallest change in status that patients consider important. Estimated MCID values for the URAM scale in the literature are 2.9 points for patients treated with NA (Beaudreuil et al 2011) and 10.5 points for those treated with open surgery (FSC or dermofasciectomy) (Rodrigues et al 2017). The results of our meta-regression analysis are consistent with these results, as we detected an improvement of 1.67 points in the URAM scale for each change in Tubiana stage (improvement of approximately 45º).…”
Section: Discussionsupporting
confidence: 88%
“…It is also consistent with the strong correlation observed between URAM and Tubiana scores in previous validations (Beaudreuil et al 2011) and with high sensitivity values reported for the DASH (Disabilities of the Arm, Shoulder and Hand) (82%) and QuickDASH (79%) questionnaires, although in these cases, meaningful change was measured using a very different methodology (Franchignoni et al 2014). The low diagnostic speci city observed (2.6%) is much lower than the rate reported for DASH (overall speci city, 74%) (Franchignoni et al 2014), although to our knowledge, the diagnostic accuracy of DASH has not yet been analyzed in the speci c setting of DC, but rather in studies analyzing different diseases (Gummesson et al 2006) or responsiveness to changes after corrective surgery for DC (Rodrigues et al 2017). Its diagnostic speci city for DC thus is unknown and is probably much lower than rates reported for general upper arm disabilities.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Despite possible objections, all these PROMs have been tested in Dupuytren’s populations ( Beaudreuil et al., 2011 ; Forget et al., 2014 ; Schoneveld et al., 2009 ; van de Ven-Stevens et al., 2015 ). The DASH was found to be unsuitable for application in this population since it lacked validity, discriminative ability and interpretability ( Forget et al., 2014 ; Rodrigues et al., 2017 ). The MHQ, which was tested in a Dutch Dupuytren’s population that had undergone percutaneous needle fasciotomy, had adequate construct validity and test–retest reliability ( Schoneveld et al., 2009 ).…”
Section: Introductionmentioning
confidence: 99%